2017
DOI: 10.1155/2017/6214083
|View full text |Cite
|
Sign up to set email alerts
|

Dengue and Scrub Typhus Coinfection in a Patient Presenting with Febrile Illness

Abstract: Dengue fever and scrub typhus are common causes of acute febrile illness of unclear origin in Asia. Though coinfections of many vector-borne diseases have been described, articles on dengue and scrub typhus coinfection are distinctly limited. In case of coinfection with dengue and scrub typhus, vigilant monitoring of vitals, platelets transfusion, and timely treatment with doxycycline are necessary. High degree of suspicion has to be made for coinfection in a patient presenting with febrile illness with thromb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 4 publications
1
21
0
Order By: Relevance
“…In the present study, we found seven leptospirosis patients to be co-infected with dengue and one with scrub typhus. Leptospirosis co-infection with dengue or scrub typhus is commonly seen in neighbouring countries such as Thailand and India [36][37][38][39][40][41][42][43]. Dengue is highly endemic in Malaysia with a minimum of 100,000 cases and more than 200 mortalities every year [44].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we found seven leptospirosis patients to be co-infected with dengue and one with scrub typhus. Leptospirosis co-infection with dengue or scrub typhus is commonly seen in neighbouring countries such as Thailand and India [36][37][38][39][40][41][42][43]. Dengue is highly endemic in Malaysia with a minimum of 100,000 cases and more than 200 mortalities every year [44].…”
Section: Discussionmentioning
confidence: 99%
“…Both these diseases peak during the monsoon and share common demographic and clinical features. Despite similarities, coinfections are exceedingly rare [8,9]. Whether this is because of the different vectors involved, a low index of suspicion or a lack of diagnostics remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…A recent case report from Nepal described coinfection of dengue and scrub typhus. 16 For this case, diagnosis of dengue was made early, with investigation for scrub typhus only considered in view of persistent symptoms. Enzyme-linked immunosorbent assay for scrub typhus returned positive, and by that time the patient had already been empirically commenced on doxycycline with a high clinical suspicion for scrub typhus infection in a known endemic area.…”
Section: Discussionmentioning
confidence: 99%